Implementasi Kebijakan Pendidikan Dengan Sistem Zonasi Dalam Penerimaan Peserta Didik Baru (PPDB) di SMP Negeri 2 Buduran - Azimatul Af’idah; Wahyu Rahmawati; Karwanto Karwanto; Ima Widiyanah (Jurnal Penelitian, 2025)
Education is a fundamental right of every Indonesian citizen guaranteed by the 1945 Constitution and strengthened by Law No. 20/2003 on the National Education System. One of the strategic policies in equalizing access to education in Indonesia is the implementation of the zoning system in the Admission of New Learners (PPDB), as regulated in Permendikbud No 17 of 2017 and refined through Permendikbud No 14 of 2018. This study aims to describe the implementation of the zoning system policy in PPDB at the junior secondary school level, especially at SMPN 2 Buduran, Sidoarjo Regency. The method used is a qualitative case study approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results showed that in general, the implementation of the zoning system at SMPN 2 Buduran went according to the provisions, including the stages of planning, team formation, technical implementation, and evaluation. However, there are still challenges such as quality gaps between schools, limited capacity, and dissatisfaction of some communitie. due to restrictions on school choices. The policy evaluation shows the need for synergy between local governments, schools and communities to improve the effectiveness of zoning implementation and ensure equity and equitable quality of education. This research contributes to policymaking at the local level to improve the zoning system in the future.